Development of a Web-Based E-SCIENCE Learning Model to Improve Science Learning Outcomes for Junior High School Students - Hardiani, Santi; Darmawan, Deni; Rahadian, Dian; Nurihsan, Juntika; Wahyudin, Dinn; Nasrulloh, Iman (Jurnal Paedagogy, 2026)
This study aims to develop a web-based E-SCIENCE learning model to improve students’ science learning outcomes on the topic of the human circulatory system. The study employed a research and development (R&D) method using the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The research was conducted at SMPN 1 Cilawu, Garut Regency, involving a sample of 40 eighth-grade students from class VIII G. The research instruments included expert validation questionnaires, student response questionnaires, and achievement tests to measure learning outcomes. The results indicate that the developed learning model meets the criteria of validity, practicality, and effectiveness. Students’ learning outcomes showed a significant improvement after the implementation of the model, as evidenced by higher post-test scores compared to pre-test scores. Furthermore, expert evaluations revealed a high level of feasibility, with both media and content experts awarding scores of 94. These findings suggest that the web-based E-SCIENCE learning model is effective in enhancing students’ understanding and learning outcomes related to the human circulatory system. Therefore, this model can be considered a viable and effective alternative for science instruction to improve student learning outcomes.